2019
DOI: 10.1186/s12873-019-0255-0
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital characteristics among patients with sepsis: a comparison between patients with or without adverse outcome

Abstract: Background The prehospital care of patients with sepsis are commonly performed by the emergency medical services. These patients may be critically ill and have high in-hospital mortality rates. Unfortunately, few patients with sepsis are identified by the emergency medical services, which can lead to delayed treatment and a worse prognosis. Therefore, early identification of patients with sepsis is important, and more information about the prehospital characteristics that can be used to identify t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 42 publications
3
19
0
Order By: Relevance
“…The fact that pain was associated with a time-sensitive diagnosis is not unexpected, as this is previously described [ 38 , 48 , 49 ]. Pain may be due to the loss of perfusion (angina, myocardial infarction) and low oxygen tension (hypoxia) with resulting inflammatory response [ 50 ].…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The fact that pain was associated with a time-sensitive diagnosis is not unexpected, as this is previously described [ 38 , 48 , 49 ]. Pain may be due to the loss of perfusion (angina, myocardial infarction) and low oxygen tension (hypoxia) with resulting inflammatory response [ 50 ].…”
Section: Discussionsupporting
confidence: 67%
“…A large proportion had a history of atrial fibrillation [8], which indicated that it was not a new finding that caused adverse illness among these patients. The fact that pain was associated with a time-sensitive diagnosis is not unexpected, as this is previously described [38,48,49]. Pain may be due to the loss of perfusion (angina, myocardial infarction) and low oxygen tension (hypoxia) with resulting inflammatory response [50].…”
Section: Discussionmentioning
confidence: 52%
“…Several of these variables are not included in previously suggested predictive tools [ 8 , 9 , 12 ]. Prior studies support that low oxygen saturation, abnormal level of consciousness, the absence of chills, fever and rigors in addition to hyperglycaemia, are predictive of poor outcome for septic patients [ 13 , 14 ]. It may be surprising that the results suggest that fever and chills are protective in sepsis, ie have a lower mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Another explanation to a better outcome could be that patients with these symptoms are more easily recognised as septic, hence receive timely treatment. Prior studies included either septic patients arriving with EMS or patients with septic shock, [ 13 , 14 ] while the current study includes all septic patients presenting to the ED-setting. Thus, is likely to include septic patients with a greater variation of disease severity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation